The effect of liquidity risk on Sharia rural banks’ profitability: The role of size and ownership - Rahmany, Sri; Widarjono, Agus; Che Arshad, Noraziah; Hendri, Zul (Universitas Islam Indonesia, 2026)
IntroductionLiquidity risk arises from its inability to meet its obligations or to fund an increase in assets at maturity without incurring unacceptable costs or losses. Accordingly, it is essential to gain a deeper understanding of the underlying relationship between bank liquidity and bank performance.ObjectivesThe goal of this study is to investigate the impact of liquidity risk on the profitability of Shariah Rural Banks (SRBs), controlling for market competition, bank-specific variables, and macroeconomic conditions. MethodThe study analyzed 154 SRBs from 2015 to 2023 using quarterly data. The total number of observations is 5,496 with unbalanced panel data. This study employs panel regression to investigate the impact of liquidity risk on profitability. ResultsThe liquidity risk decreases profitability. Small SRBs encounter more risks related to liquidity risk than large Islamic banks. The local state-owned SRBs are more effective in mitigating the negative impact of funding risk on profitability. Also, strong market power and bank fundamentals support profitability. Furthermore, a good economic condition boosts profitability. ImplicationsFirst, policymakers must oversee the liquidity risk management of SRBs to ensure that the negative impact of mismatched maturity on profits is relatively small. Second, SRB must effectively manage liquidity risk by carefully selecting customers and closely monitoring financing when they are at high liquidity risk.Originality/NoveltyThe empirical research on the impact of liquidity risk on SRB's profitability is still rare to date. Our research explores the effect of liquidity risk on profitability, considering bank size and bank ownership as moderating variables.